Misrepresentation of health research in exertion games literature - Marshall, Joe; Linehan, Conor (2017)
HCI often requires scholars to build upon research from fields outside their expertise, creating the risk that foundational work is misunderstood and misrepresented. The prevailing goal of “exergames” research towards ameliorating obesity appears to be built on just such a misunderstanding of health research. In this paper, we analyse all citations to a single influential study, which has been extensively cited to justify research on exergames. We categorise the 375 citations based on whether they represent the findings of that study accurately or inaccurately. Our findings suggest that 69% of exergames papers citing this study misrepresent the findings, demonstrating a systematic failure of scholarship in exergames research. We argue that exergaming research should cease focusing on games as treatment for obesity, and that HCI publications should demand more critical and scholarly engagement with research from outside HCI.